Efektifitas Motor Relearning Program dalam Meningkatkan Pemulihan Motorik Ekstremitas Atas dan Kemandirian Aktivitas Berpakaian Pasien Pasca Stroke - Khairul Anam, Muhammad; Kurniawan, Hendri (Politeknik Kesehatan Kemenkes Surakarta, 2023)
Background: Upper extremity motor disorders are the main complaint in the majority of post-stroke patients. Motoric ability is an important prerequisite in daily activities (activities of daily living), including dressing. Motor Relearning Program (MRP) is a method to train the motor skills of post-stroke patients. Objectives: The aim of this study was to examine the effectiveness of MRP on upper extremity motor recovery and its effect on the ability to dress activities in post-stroke patients. Methods: The study was conducted with a one-group pretest-posttest pre-experimental design. The research sample was obtained by purposive sampling. The instruments used in this study were the Fugl-Meyer Upper Extremity (FMA-UE) and the Nottingham Stroke Dressing Assessment (NSDA). Data processing was carried out by means of comparative tests and regression tests using SPSS 25 software. Results: The majority of the respondents were male (65%), elderly (65%), <24 months of onset (75%), and with right hemisphere lesions (60%). The mean ± SD FMA-UE score was 37.75 ± 8.63 (pretest) and 47 ± 6.44 (posttest). The mean ± SD NSDA were 8.10 ± 2.94 (pretest) and 12.40 ± 2.89 (posttest). The comparison test showed a significant difference in the FMA-UE score (z=-3.924, p<0.05) and the NSDA score (z=-3.927, p<0.05). The linear regression test shows p-value = 0.001 with a determinant coefficient of 0.459. Conclusion: The MRP method is effective in improving the recovery of upper extremity motor skills in post-stroke patients, which has an effect of up to 45.9% on improving the dressing ability of post-stroke patients. Keywords : Stroke, Motoric, MRP, Dressing